Midlands State University student cyber deferment system - Makiwa, Tinashe (Midlands State University, 2016)
Midlands State University Student Cyber Deferment System is an online-computing solution system that allows the current students to defer and resume their studies online and receive the confirmation via email. Student cyber deferment system will give more room to access the information of the student who deferred their studies through use of various cyber computing platforms provided by the system for example 3D Bar and linear graphs .Interviews, questionnaires and observation where used as data gathering methodologies and it was found out that students have to come over to campus to do the deferment process thus time consuming and tiresome and it was difficult to produce a record of student who has deferred their studies during a period of time. The system helps to secure and provide efficient means of carrying out the student deferment processes.